Red social en la comercialización de cacao del sitio San Miguel de Brasil, parroquia Rio Bonito del cantón el Guabo, provincia de El Oro, 2012. - Herrera Luzón, Fernando (2016)
The present investigation “SOCIAL NETWORK IN COMMERCIALIZATION ED COCOA of the PLACE SAN MIGUEL ED BRAZIL, PARISH CHURCH LAUGHED NICE of the CANTON THE GUABO, HIS PROVINCE GOLD, PERIOD 2012”, constitute an analysis of the situation and kinds of commercialization of the cocoa produced by the little producers located in the jurisdictions of San Miguel of Brazil. The main diagnosed problems are related to the processes cropping, maintenance, harvest and basically with the commercialization of pickpocket, since when is about proprietary and leasing producers of farms of between 2 and 5 hectares, production is median, where the sale is accomplished by the prices for tin cans harvested, to the intermediaries, logically also they are speculative, having to adapt to a system that proves to be exploitative for them.